Indivisibiliter ac inseparabiliter? Térszerkezeti változások egy összetartozó térségben. Ausztria és Magyarország - Tóth, Imre (Közép-Európai Közlemények, 2009)
By the beginning of the 20th century significant regional differences appeared on the territory of the historic Hungary. West-Hungary was one of the mostly developed region partly because its closeness to Wien and of the Austrian–Hungarian economic cooperation. After the First World War the border between Austria and Hungary blocked this cooperation. Our paper presents this cooperation from 1920 until now.